UID2023. TRANSITIONS. Cross Modulate Develop. 44th International Conference of Representation Disciplines Teachers (diségno, 2023)
The 44th International Conference of Representation Disciplines Teachers, Congress of Unione Italiana per il Disegno, opened in the Sala delle Capriate of Palazzo Steri, seat of the rectorate of the University of Palermo. The institutional greetings preceded the celebrations of the awarding of “Benemerite alla memoria” to Margherita De Simone and Rosalia La Franca, founders of the Palermo ‘drawing school’, who contributed to the transition of the disciplines of Drawing from the ‘limit of geometric  instrument’ towards representation of space in its physical and conceptual narrative’. We remember the Seminari di Primavera, organized in Palermo in which innovative representative procedures were tested for drawing as a language of sharing and methodologies for developing new research practices. [read more]